The Urgency of Halal Product Certification for Tourist Destinations in Realizing Global Halal Tourism - Jauhariyah, Nur Anim; Syafa’at, Ahmad Munib; Mahmudah, Mahmudah (Proceedings of Annual Conference for Muslim Scholars, 2025)
Halal tourism has become a key sector in the development of the global tourism industry, as the increasing number of Muslim tourists demand assurance of halal-certified products and services. Halal product certification plays a strategic role in providing certainty, safety, and comfort for Muslim tourists, while also strengthening the competitiveness of tourist destinations internationally. This study aims to examine the urgency of halal certification for products in tourist destinations and its implications for the realization of global halal tourism. This study uses a quantitative descriptive approach using secondary data that describes the conditions of tourism visits and halal products in Banyuwangi Regency. The findings indicate that halal certification is not only an instrument of legal certainty and consumer trust but also a global branding strategy that can increase added value, expand market reach, and strengthen Indonesia's position in the global halal tourism arena. Therefore, accelerating halal product certification in tourist destinations, especially in Banyuwangi Regency, is an important step in realizing sustainable halal tourism.